Tata Kelola Keuangan Sekolah - Suyati, Suyati (AL-IDARAH: JURNAL KEPENDIDIKAN ISLAM, 2020)
The author writes this paper in order to analyze the correlation of the educational background of the educational staff to individual performance in school finance and financial management in general. In the management of school finances it is not 'easy' but what is needed is the name of accuracy, accuracy, transparency, accountability, as well as effective and efficient. To achieve this, of course, education staff are needed in accordance with the potential in their fields. With an optimal workforce, the work results are also optimal. Thus the administration of school finance will be better directed and better. Specifically this paper will discuss how the school financial management is theoretically linked to the actual financial management, starting from the understanding of financial management, the process of school financial management and the accountability of financial management of educational institutions / schools, and finally whether there is a correlation of the latest education workforce towards individual performance in the field of finance or in other words in managing school finances. Keywords: Education, labor, school finance